Sosialisasi Dan Pelatihan Inovasi Makanan Sehat Sebagai Ide Bisnis Di Kelurahan Kepanjen Kidul,Blitar - Cita Devi Ainaya; Niniek Imaningsih; Cholid Fadil (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Kepanjen Kidul Village is one of the villages in Kepanjen Kidul District, Blitar City, East Java Province. One of the problems faced is the lack of awareness of MSME actors about the importance of digital marketing to advance their business. This sub-district is the city center so it must be able to show special culinary delights for tourists from outside the city so they can find out more about Blitar City. This community service activity aims to provide training in making healthy food, namely "Fried Shredded Egg Omelette" which can later be used as a new business idea for MSMEs. This activity was also supported by socialization regarding digital marketing and the use of the Canva application to support their business. The activity was held on June 13 2023 which was attended by 15 participants. The material presented in the training activities is the process of making, decorating, and also packaging the Shredded Egg Omelette. The method used is socialization and training with the aim of being able to provide knowledge to the community and continued training methods so that they can maximize the knowledge gained during the socialization. The implementation of the activity was carried out with socialization regarding digital marketing and then continued with training on making healthy food. After this activity is carried out, it is hoped that it will increase knowledge about digital marketing, use the Canva application and understand about managing healthy food, decorating and packaging a product.